2022
DOI: 10.1021/acssensors.1c02113
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Fluorometric Detection of SARS-CoV-2 by Targeting the G-Quadruplex through pH-Triggered Conformational Polymorphism

Abstract: Unravelling unique molecular targets specific to viruses is challenging yet critical for diagnosing emerging viral diseases. Nucleic acids and proteins are the major targets in diagnostic assays of viral pathogens. Identification of novel sequences and conformations of nucleic acids as targets is desirable for developing diagnostic assays specific to a virus of interest. Here, we disclose the identification and characterization of a highly conserved antiparallel G-quadruplex (GQ)-forming DNA sequence present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…32 Doxorubicin, a clinically approved drug against SARS-CoV-2 infection, also was known as a G-quadruplex ligand, which provided potential clinically targets for the prevention and treatment of SARS-CoV-2. 33,34 In our study, the activity of ATF4 expression was enhanced in ferroptotic HepG2 cells induced by erastin. In the meantime, the preliminary bioinformatics analyses suggested that the regions of the ATF4 promoter also contained characteristic forming-motifs of G4.…”
Section: ■ Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…32 Doxorubicin, a clinically approved drug against SARS-CoV-2 infection, also was known as a G-quadruplex ligand, which provided potential clinically targets for the prevention and treatment of SARS-CoV-2. 33,34 In our study, the activity of ATF4 expression was enhanced in ferroptotic HepG2 cells induced by erastin. In the meantime, the preliminary bioinformatics analyses suggested that the regions of the ATF4 promoter also contained characteristic forming-motifs of G4.…”
Section: ■ Introductionsupporting
confidence: 50%
“…Moreover, the functional G4 structures contained in the long terminal repeat (LTR) promoter regions could significantly inhibit the replication of HIV-1, and the BRACO-19 ligand exhibited striking anti-HIV-1 activity . Doxorubicin, a clinically approved drug against SARS-CoV-2 infection, also was known as a G-quadruplex ligand, which provided potential clinically targets for the prevention and treatment of SARS-CoV-2. , …”
Section: Introductionmentioning
confidence: 99%
“…This sequence changes from the duplex form to the G4 structure in a pH-dependent manner. Thereafter, the authors developed a reliable fluorometric detection of SARS-CoV-2 by targeting this DNA G4 through pH-triggered conformational changes [157] . Furthermore, G4-based aptamers against proteins have been used in disease diagnosis and therapy [153] .…”
Section: G4s As Biosensors For Sars-cov-2 Detectionmentioning
confidence: 99%
“…However, differentiating macrophages (M1 and M2) is mainly based on different biomarkers like the cytokine expressed in the two different phenotypes of macrophages. This involves immunohistochemistry, which is tedious and expensive. As an alternative, small molecular fluorescent probes are promising diagnostic tools due to their simplicity, cost-effectiveness, and high sensitivity with good resolution. Moreover, a molecular fluorescent probe detecting hypochlorite (OCl – ) that can differentiate different macrophages is not known, as per our knowledge.…”
Section: Introductionmentioning
confidence: 99%